Cable vibrations in cable-stayed bridges - Caetano, Elsa de Sá, 1965- (IABSE, 2007)
"The fifty years of experience of construction of cable-stayed bridges, since their establishment as a new category among the classical types, have brought an immense progress, ranging from design and conception to materials, analysis, construction, observation, and retrofitting. The growing construction of cable-stayed bridges have attracted the attention of researchers and designers to the problem of cable vibrations. Intensive research has been developed all over the world during the last two decades as a consequence of the numerous cases of cable vibrations exhibited by all types of cable-stayed bridges. Despite the increased knowledge of the various vibration phenomena, most of the outcomes and research results have been published in journals and conference proceedings and scarce information is currently provided by the existing recommendations and codes. This book provides a comprehensive survey on the governing phenomena of cable vibration, both associated with direct action of wind and rain: Buffeting, vortex-shedding, wake effects, rain-wind vibration; and resulting from the indirect excitation through anchorage oscillation: External and parametric excitation. Methodologies for assessment of the effects of those phenomena are presented and illustrated by practical examples" Description from Knovel site
Keywords: Cable-stayed bridges -- Vibration.; Cables -- Vibration.; elektronické knihy; electronic books